Evidence for Phytophthora cinnamomi involvement in Iberian oak decline (Plant Pathology, 1993)
Rapid and sometimes extensive mortality and decline of oak, principally Quercus suber and Q. ilex, has occurred in parts of southern Spain and Portugal in recent decades. We report here isolation of the aggressive root pathogen Phytophthora cinnamomi from roots of diseased oaks or from soil at eleven out of thirteen decline foci examined. It is proposed that the introduction and spread of P. cinnamomi may be a major factor in the Iberian oak decline, interacting with drought and other site factors, and leading to stress-related attacks by insects and other fungi. By analogy, it may also be involved in the similar oak declines occurring elsewhere on the Mediterranean.